2022
DOI: 10.3389/fpls.2022.828482
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis and Expression Profiles of Ethylene Signal Genes and Apetala2/Ethylene-Responsive Factors in Peanut (Arachis hypogaea L.)

Abstract: Peanut is an important oil and economic crop widely cultivated in the world. It has special characteristics such as blooming on the ground but bearing fruits underground. During the peg penetrating into the ground, it is subjected to mechanical stress from the soil at the same time. It has been proved that mechanical stress affects plant growth and development by regulating the ethylene signaling-related genes. In this study, we identified some genes related to ethylene signal of peanut, including 10 ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…The number of AP2/ERF genes was greatest on chromosome 2 (22), chromosome 16 had the fewest (5), and the number on the other chromosomes ranged from 7 to 21. Most of the genes were on both ends of the chromosomes, which was similar to studies in Arabidopsis and other species [ 5 , 32 , 33 ]. The distribution similarity of genes on chromosomes indicates functional consistency.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The number of AP2/ERF genes was greatest on chromosome 2 (22), chromosome 16 had the fewest (5), and the number on the other chromosomes ranged from 7 to 21. Most of the genes were on both ends of the chromosomes, which was similar to studies in Arabidopsis and other species [ 5 , 32 , 33 ]. The distribution similarity of genes on chromosomes indicates functional consistency.…”
Section: Resultssupporting
confidence: 84%
“…Analyzing the exon-intron structure of the JmAP2/ERF gene revealed that 64 members of this family possessed introns, including 27 JmAP2 genes, 2 JmRAV genes, 4 JmSoloist genes, 9 JmDREB genes, and 22 JmERF genes. Among them, the JmAP2 subfamily contained more introns than other families; however, zero or few introns were observed in the JmERF and JmDREB subfamilies; similar results have been found in C. olitorius L. [ 12 ], A. hypogaea L. [ 32 ], and C. illinoinensis [ 33 ]. This seemed to be related to the 122 pairs of segmental duplication events in this study and further confirmed that segmental duplication leads to intron loss with a higher probability than gain [ 36 ].…”
Section: Discussionsupporting
confidence: 68%
“…The FPKM value of EIN3 was upregulated by 2.38 times in the L3S vs. D3S comparison in response to light ( Figure 5E ). Our previous study also showed that EIN3 was significantly expressed during pod development ( Cui et al, 2022 ). Three JAZ ( NLIW19 , 76C240 , and W1F2QM ) were significantly upregulated after the loss of mechanical stress and darkness.…”
Section: Resultsmentioning
confidence: 70%
“…In recent years, extensive studies have revealed the key regulatory roles of auxin, ethylene, cytokinin, abscisic acid, and gibberellin in peanut pod development, maturation, and response to biotic/abiotic stresses. 36,37 The comparative transcriptome data present in this study showed that plant hormone signaling pathway genes in the peanut pod varied greatly when faced with microplastics contamination and biochar amendment, especially those involved in the auxin signal transduction pathway. All high-abundance DEGs of the auxin signal transduction pathway exhibited opposite expression trends in the comparisons T1-v-T2 and T2-v-T3.…”
Section: Discussionmentioning
confidence: 83%